From Compliance to Commitment: The Role of Culture in Embedding ESG into Corporate Governance - Alexandrova, Nedyalka (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
The integration of Environmental, Social, and Governance (ESG) principles into corporate governance has become a central element of contemporary management and regulatory discourse. While formal ESG compliance has expanded rapidly in response to regulatory pressure and stakeholder expectations, the depth and effectiveness of ESG implementation vary significantly across organizations and institutional contexts. This paper argues that culture plays a critical mediating role in shaping whether ESG adoption remains a compliance-driven exercise or evolves into a genuine organizational commitment embedded in governance structures and strategic decision-making. Drawing on insights from institutional theory, organizational culture, and cross-cultural management, the paper develops a theoretical framework that explains how national and organizational cultural characteristics influence the internalization of ESG values. The analysis highlights how dimensions such as trust, long-term orientation, power distance, and uncertainty avoidance affect managerial attitudes, governance practices, and the legitimacy of ESG initiatives. The paper contributes to the literature by conceptualizing the transition from compliance to commitment as a culturally contingent process and by identifying the conditions under which ESG becomes a substantive driver of sustainable corporate governance rather than a symbolic or procedural requirement.